Effect of bio-functional MAO layers on the electrochemical behaviour of highly porous Ti - Alves, A. C.; Costa, A. I.; Toptan, F. [UNESP]; Alves, J. L.; Leonor, I.; Ribeiro, E.; Reis, R. L.; Pinto, A. M.P.; Fernandes, J. C.S. (Elsevier, 2020)
Ti foams are attractive for orthopaedic applications due to reduced Young's modulus and ability of bone in-growth. However, poor corrosion behaviour and lack of bioactivity are yet to be overcome. In the present work, highly porous Ti samples were processed by powder metallurgy with space holder technique and bio-functionalized by micro-arc oxidation, resulting in nano/micro structured TiO2 surfaces containing bioactive elements. The electrochemical behaviour of these bio-functionalized highly porous Ti surfaces was evaluated through potentiodynamic polarization and EIS in physiological solution at body temperature. Results showed that bio-functionalization improved the corrosion behaviour of highly porous Ti. However, increased macro-porosity led to an increased corrosion rate.
Keywords: Corrosion; EIS; Micro-arc oxidation; Porous Ti; Powder metallurgy